Validation of the PROMIS-57 and PROMIS-29 Profile Questionnaires in Kidney Transplant Recipients. (July 2018) - Tang, Evan; Bansal, Aarushi; Cao, Sarah; Edwards, Nathaniel; Li, Madeline; Novak, Marta; Mucsi, Istvan
Abstract : Background: The Patient Reported Outcomes Measurement Information System (PROMIS) aims to address the lack of generalizable and universal measure of patient reported outcomes to assess many health-related quality of life domains. It has undergone extensive psychometric testing for validity and reliability but it has not been tested among patients with chronic kidney disease. Here, we validate the PROMIS-57 and the PROMIS-29, questionnaire among kidney transplant recipients. Methods: A cross-sectional, convenience sample of stable kidney transplant recipients was recruited. Each participant completed the PROMIS-57, a 57-question instrument that measures 7 domains – physical function, anxiety, depression, fatigue, pain, sleep disturbance, and social functioning – alongside validated legacy questionnaires (Patient Health Questionnaire (PHQ9), General Anxiety Disorder (GAD7), Edmonton Symptom Assessment Scale (ESAS), and Kidney Disease Quality of Life (KDQoL-36)). PROMIS-29, a 29-question instrument is nested within PROMIS-57 and measures the same domains. Structural validity of PROMIS was assessed using confirmatory factor analysis and reported using the Tucker Lewis Index (TLI) and Comparative fit index (CFI). Construct validity was assessed with known group comparisons. Internal consistency was assessed with Cronbach's α and convergent validity was assessed through Spearman's Rho. Test-retest reliability was assessed through the intraclass coefficient (ICC). Results: Mean (±SD) age of the 179 participants was 51 (±17), 57% were male, and 55% Caucasian. Internal consistency of each domain was high (Cronbach's α>0.90 for each). Confirmatory factor analysis showed good structural validity (TLI and CFI > 0.95 for most domain measures). PROMIS anxiety demonstrated strong correlation with GAD7 (PROMIS-57: rho=0.760, 95%CI:0.683-0.820; PROMIS-29: rho=0.730, 95%CI:0.645-0.798). PROMIS depression demonstrated correlation with PHQ9 (PROMIS-57: rho=0.676, 95%CI:0.578-0.755; PROMIS-29: rho=0.634, 95%CI:0.526-0.721). PROMIS physical function demonstrated strong correlation with the KDQol-36 physical composite score (PROMIS-57: rho=0.806, 95%CI:0.745-0.853; PROMIS-29: rho=0.789, 95%CI:0.723-0.840). PROMIS fatigue demonstrated strong correlation with ESAS fatigue (PROMIS-57: rho=0.722, 95%CI:0.636-0.790; PROMIS-29: rho=0.725, 95%CI:0.640-0.792). Test-retest reliability indicated good agreement, with ICC>0.6 for all. Known group comparisons also supported validity. Conclusions: Our results confirmed that the PROMIS-57 and the PROMIS-29 profile are highly reliable and valid instrument among kidney transplant recipients. We propose it is a valuable tool to assess domains of the disease experience that are relevant and important for patients. Further studies are needed to examine the validity and reliability of computer adaptive testing to reduce questionnaire burden.